2020
DOI: 10.21608/bvmj.2020.37742.1237
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Aeromonas spp and their virulence factors isolated from frozen chicken meat products

Abstract: A total of hundred samples of frozen chicken products represented by breast, thigh, nuggets and burger (25 of each) were randomly collected to study the prevalence of Aeromonas spp and their virulence factors in the examined products. the study showed that the mean values of psychrotrophic count were 8.17×10 3 ± 1.42×10 3 , 1.95×10 4 ± 2.06×10 4, 3.63×10 4 ± 0.89×10 4 and 7.58×10 4 ± 1.16×10 4 , respectively, and the mean values of Aeromonas counts were 9.34×10 2 ± 2.01×10 2 , 1.66×10 3 ± 0.28×10 3 , 2.90×10 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…mirabilis (18.6%), and S . aureus (8.5%); findings that corroborate previous studies ( Kitai et al, 2005 ; Brahmabhatt, 2011 ; Beninati et al, 2015 ; Owuna et al, 2015 ; Skočková et al, 2015 ; Bortolaia et al, 2016 ; Davis et al, 2018 ; Li et al, 2019 ; Sanches et al, 2019 , 2021 ; Sarker et al, 2020 ; Sheir et al, 2020 ; Yu et al, 2021 ). During slaughter, carcasses are likely contaminated at various stages of processing by the microbial flora from the digestive tract, skin, and feathers, as well as by bacteria present on surfaces on processing equipment and in the chillers ( Rouger et al, 2017 ).…”
Section: Resultssupporting
confidence: 88%
“…mirabilis (18.6%), and S . aureus (8.5%); findings that corroborate previous studies ( Kitai et al, 2005 ; Brahmabhatt, 2011 ; Beninati et al, 2015 ; Owuna et al, 2015 ; Skočková et al, 2015 ; Bortolaia et al, 2016 ; Davis et al, 2018 ; Li et al, 2019 ; Sanches et al, 2019 , 2021 ; Sarker et al, 2020 ; Sheir et al, 2020 ; Yu et al, 2021 ). During slaughter, carcasses are likely contaminated at various stages of processing by the microbial flora from the digestive tract, skin, and feathers, as well as by bacteria present on surfaces on processing equipment and in the chillers ( Rouger et al, 2017 ).…”
Section: Resultssupporting
confidence: 88%
“…In the current study, the results illustrate that Aeromonas species were isolated from barbecued chicken meat (11.1%) and grilled fish (27.3%). The results of previous studies [2,39] coincided with ours as Aeromonas species were isolated from ground chicken meat. Other studies reported higher levels of contamination by Aeromonas species (47.17% and 57%) in chicken meat samples, respectively [40,41].…”
Section: Discussionsupporting
confidence: 90%
“…However, RTE foods can be involved in probable health risks due to their potential microbial contamination with foodborne pathogens at any stage of food chain preparation [1]. When RTE foods are handled in unsanitary circumstances where pathogenic bacteria exist in the equipment, workers' aprons/hands, and surrounding environment, the final RTE food end product could be contaminated [2]. The major foodborne pathogens that could infect humans through ingestion of contaminated food are, for example, Staphylococcus aureus, Salmonella spp., Vibrio cholera, Streptococcus spp., Klebsiella pneumoniae, Micrococcus spp., Clostridium botulinum, Aeromonas hydrophila, Escherichia coli, Bacillus spp., Enterobacter cloacae, Egypt Acinetobacter, Proteus mirabilis, Pseudomonas species, Citrobacter freundii, and Serratia species.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial count was expressed as log CFU ml −1 for water and fish samples. The total bacterial count was enumerated on a plate count agar (PCA) previously supplemented with 100 μl of each dilution (fish and water samples), then incubated at 37°C for 1 day (Saad et al, 2021), while the Aeromonas count was calculated on an Aeromonas agar medium after 1 day of incubation at 37°C (Sheir et al, 2020). The Aeromonas spp., colonies were distinguished by dark green with blackcentered colonies.…”
Section: Total Bacterial and Aeromonas Spp Count In Water And Fish Ti...mentioning
confidence: 99%